The importance of biopsy in clinically diagnosed metastatic lesions in patients with breast cancer - Abedallaa, Nader (Latakia University Journal -Medical Sciences Series, 2018)
Background: Receptor status discordance, such as estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor 2 (HER2) status between primary breast cancer and metastatic lesions has been reported. The aim of this study was to evaluate the biopsy of clinically diagnosed metastatic lesions and to determine the changes in hormonal receptor and HER2 status of the metastatic lesions Methods: 74 patients with clinically diagnosed metastatic breast cancer underwent an excisional biopsy or core needle aspiration guided by computed tomography/ultrasound. ER, PR and HER2 were assessed by immunohistochemistry (IHC). Results: A total of 58 metastases (78.3%) and nine second primary malignancies (12.1%), five primary lung cancers, on primary pancreatic cancers, tow non hodjkine lymphoma and on hodjkin lymphoma were found. The discrepancies between ER, PR and HER2 status between the primary breast cancer and metastatic lesions were 15.5%, 18.9% and 12%, respectively. Six lesions (9.4%) were proved benign upon biopsy. Conclusions: The biopsy of clinically suspicious metastatic lesions could histologically confirm the diagnosis of metastasis, evaluate discrepancies between ER, PR and HER2 status and exclude secondary malignancy, which might change the therapeutic strategy for breast cancer patients. الأهمية السريرية لإجراء خزعة من الأفات النقائلية في سرطان الثدي الناكس لقد تم تأكيد الاختلاف في طبيعة مستقبلات الاستروجين (ER), مستقبلات البروجسترون (PR) ومستقبلات عوامل النمو الغشائية 2 (HER2 ) بين الورم البدئي والنقائل المكتشفة لاحقا. تهدف هذه الدراسة الراجعة إلى تأكيد النكس من سرطان الثدي واستقصاء المستقبلات الهرمونية ومستقبلات عوامل النمو الغشائية2 (ER,PR,HER2) ودراسة نسبة الاختلاف في التعبير عنها في الأفات النقائلية مقارنة بالورم البدئي بالاضافة لاستخدامها كعوامل تنبؤية هامة في الاستراتيجية العلاجية عند هذه المجموعة من المرضى. شملت الدراسة 74 مريضة من المراجعين لمركز المعالجة الكيميائية والشعاعية في مشفى تشرين الجامعي بين آذار 2011 وأيار 2016 لديهن سرطان ثدي نقائلي مكتشف حديثا بعد جراحة استئصالية للثدي ومعالجة إضافية, أجري لجميع المريضات خزعة جراحية أو خزعة موجهة بالايكو أو الطبقي المحوري من الأفات النقائلية وقبل البدء بالمعالجة , أجري لجميع المريضات دراسة نسيجية للخزعة لتأكيد التشخيص ثم اجراء دراسة للمستقبلات (ER,PR,HER2 ) في حال كانت النقائل من سرطان الثدي. تم تشخيص نقائل ورمية من سرطان الثدي عند 58 مريضة (78,3%), ولوحظ اختلاف التعبير عن المستقبلات الهرمونية ER,PR بين الورم البدئي والنقائل عند (15,5%) و (18,9%) على التوالي كما لوحظ اختلاف التعبير عن HER2 عند 7مرضى فقط وبنسبة (12%).9 حالات ورمية ثانوية جديدة وبنسبة (12,1%) شخصت بالخزعة منها 5 حالات ورم رئة , حالة ورم بنكرياس , حالتان لمفوما لاهودجكين وحالة لمفوما هودجكين بالإضافة لوجود7 حالات لإصابات سليمة بدون وجود أفات خبيثة وبنسبة (9,4% ). يجب اجراء خزعة روتينية لكل الآفات المشتبهة الظاهرة بعد معالجة شافية لسرطان ثدي بدئي لتأكيد النكس من سرطان الثدي واستبعاد الأورام الثانوية والأفات السليمة مع ضرورة إجراء دراسة جديدة للمستقبلات (ER,PR,HER2 ) على الأفات النقائلية من سرطان الثدي لنتمكن من وضع الاستراتيجية العلاجية المثالية